THU0620 Persistence with biological disease-modifying antirheumatic drugs – a retrospective database study in japanese patients with rheumatoid arthritis. (15th June 2017) - Mahlich, J; Kameda, H; Sruamsiri, R
Abstract : Background: Persistence rate is one of the key benefits of biological disease-modifying antirheumatic drugs (bDMARDs) in the treatment of rheumatoid arthritis (RA). Limited evidence of persistence has been found in Japan and the results are not transferrable across countries and cultures (1–3). In addition, the impact of persistence on healthcare cost is still questionable. Objectives: To assess persistence rates of bDMARDs for the treatment of RA in Japan and compared resource utilization and treatment costs between persistence and non-persistence groups. Methods: Data was extracted from a Japanese claims database that included 4, 400, 000 patients between 2009 and 2015. RA patients who initiated bDMARD treatment (bDMARD-naïve patients) were identified and included in the final analysis. Survival analysis was used to estimated 6-, 12-, and 18- month persistence rates for current bDMARDs. Propensity score matching was applied to control for potential treatment selection bias. Resource utilization and health care costs of treatments were calculated 12 months before and after initiation of bDMARDs treatment and compared between persistence and non-persistence groups. Results: A total of 6, 153 bDMARD-naïve patients were included in the final analysis. The overall 1-year persistence rate was 85% (95% CI, 84–86). Persistence of patients treated with golimumab was higher [92% (95% CI, 89–94)] than that with other bDMARDs. Overall, 1-year outpatient visits increased from 10 at baseline to 16 after bDMARD treatment, while the number of hospital admissions declined from 3.3 to 1.6. Hospital days decreased from 17 at baseline to 12 following treatment. The non-persistence group had a larger increase in outpatient visits after bDMARD initiation compared with the persistence group (8 to 16 vs. 10 to 16, respectively) and a smaller decrease in hospital admissions (3.1 to 1.9 vs. 3.5 to 1.4, respectively). Compared to non-persistence group, persistence was associated with a reduction in total healthcare costs of 760 USD. Conclusions: Japanese bDMARD-naïve patients with RA have a high persistence rate of bDMARDs. The reduction in medication costs in non-persistent patients is offset by higher hospitalization costs, making non-persistence more expensive. References: Dalén J et al. Rheumatol Int 2016;36(7):987–95. Tang B et al. Clin Ther 2008;30(7):1375–84. Meissner B et al. J Med Econ 2014;17(4):259–65. Disclosure of Interest: J. Mahlich Employee of: Janssen Pharmaceutical KK, H. Kameda Grant/research support from: Abbvie GK, Astellas Pharma, Chugai Pharmaceutical Co, Ltd., Eisai Co. Ltd., Mitsubishi Tanabe Pharma Co., Nippon Kayaku Co. Ltd., Santen Pharmaceutical Co. Ltd., Takeda Pharmaceutical Co. Ltd, Consultant for: Eli Lilly Japan K.K., Novartis Pharma K.K. and Sanofi K.K., Speakers bureau: AbbVie GK, Astellas Pharma, Bristol– Myers K.K., Chugai Pharmaceutical Co. Ltd., Eisai Co. Ltd., Janssen Pharmaceutical K.K., Mitsubishi Tanabe Pharma Co., Nippon Kayaku Co. Ltd., Pfizer Japan Inc., Santen Pharmaceutical Co. Ltd. and Takeda Pharmaceutical Co. Ltd. and UCB Pharma, R. Sruamsiri Employee of: Janssen Pharmaceutical KK